PENINGKATAN SERAT PANGAN LARUT DARI AMPAS TAHU DAN SIFAT FUNGSIONALNYA DENGAN PERLAKUAN FISIK: TINJAUAN LITERATUR - Rizki Aristyarini; Sedarnawati Yasni; Elvira Syamsir (Jurnal Teknologi Industri Pertanian, 2022)
Tofu processing leaves by-product in the form of tofu dregs whose the utilization as food is still limited. Tofu dregs contain higher insoluble dietary fibre (IDF) than the soluble dietary fibre (SDF). SDF components have wider range of health benefits, and they tend to contribute better to food processing. This study aimed to analyse the potential of physical treatment to increase in SDF tofu dregs, examine changes in its functional properties, and determine the potential physical treatment applied in Indonesia based on the SDF profile. Research data from scientific literature namely research journals, master theses, undergraduate theses, and scientific reviews were collected and analyzed descriptively. The results of descriptive analysis of the literature showed that the physical treatments identified were combination of HHP and autoclave, steam explosion, combination of single screw extrusion and alkaline solution, double screw extrusion, BEP double screw extrusion, and autoclaving. Physical treatment on all instruments can increase the SDF content of tofu dregs. The water retention capacity (WRC) and swelling capacity of tofu dregs increased after being treated with combination of HHP and autoclave, double screw extrusion, and BEP double screw extrusion. The oil holding capacity (OHC) increased after being treated with combination of HHP and autoclave, and double screw extrusion, but the WRC and OHC decreased in the steam explosion treatment. The solubility of tofu dregs increased after being given steam explosion and autoclave. Changes in the functional characteristics of tofu dregs expand their potential for use in specific processed foods. Keywords: tofu dregs, physical modification, soluble dietary fiber, food processing